BAURAN PEMASARAN DAN LOYALITAS KONSUMEN HANDPHONE BLACKBERRY - Amron Amron (Jurnal Ilmiah Infokam, 2015)
This  study used  asample ofBlackBerry mobile phoneusersinKudus with 103respondentsThis sample  usingcriteria:the  respondentswhohave  usedandhave  aBlackBerry  mobile  phonealeast1year.Samplingtechniqueusingpurposive samplingisa sampling techniquebased onacertaintype ofpersonwhocanprovidethe appropriate informationthathas beenset bytheresearchers.  Data collection techniques inthis study usingan ordinalscalewhilemakingtechniquereferstothe Likertscale. This research has found that the  biggest  variableaffectedtheconsumerloyaltyis aqualityproduct,  it indicatesthatthe  BlackBerrycontinuestomaintainandimprove thequality of its products, among others,  by improvingfeaturespackaging(casing),  colorvariationandthe like.Smallestvariablesthat affectconsumerloyaltyistheprice,  expectedBlackBerrymight  consider  includingthe  pricevariablesin makingpoliciesrelated  toenhancingcustomer loyalty.  For example by applyingthe priceaccording tothetargetsegmentandcompetitioncurrentlyworked byBlackBerry.Keywords: product, price, distribution, consumerloyalty.